Spatial Correlates of Gun Deaths in Harris County, Texas - Levine, Ned (Homicide studies, 2021)
Firearm homicide and suicide deaths for 2014 were examined in Harris County, Texas, for spatial variation and socio-economic correlates. Higher firearm homicide rates were found closer to central Houston than firearm suicide rates. Local hot spots were identified for both types but overlapped at only two locations. A Poisson–Gamma–Exposure regression model showed the homicide rate was associated with higher percentages of persons who are Black, aged 15 to 29 years, and living in poverty whereas the suicide rate was associated with a higher percentage of persons of non-Hispanic White ethnicity. Firearm policies that reduce homicides may also reduce suicides.